A Study of Blood Glucose Level in the Newborn - Muzief Munir; T. Husada; R. E. J. Rotty (Indonesian Pediatric Society, 1980)
One hundred and thirteen newborns admitted to the nursery ward of the Child Health Department from June 1, 1976 until December 31, 1976 were selected for this study. They were, 34 normally delivered term infants, 26 SGA with birth-weight ranging 1750-2400 gm and 30 high risk term infants and 23 premature. Blood glucose was examined at l, 3 and 6 hours after birth using 0-Toluidine method. It was found that in the normal term infants there was a significant increase of mean blood glucose level at 3 hours after birth (p<0.05), followed by a slight decrease at 6 hours of age. In small for gestational age and premature infants a slight increase was observed at 3 hours of age, followed by a moderate but insignificant decrease at 6 hours of age. In the high-risk-term-infants, almost no fluctuation of blood glucose level was detected throughout the study. This study shows that 6-hour-fasting period for normal term, S.G.A. and premature infants with birth weight ranging from 1750-2500 grams, and high risk-term infants is justified to be safe with regard to the risk of hypoglycemia.